Registering mortgages in the real estate cadastre based on a mortgage agreements and implementing changes to mortgaged properties - Bodrožić Milana (Glasnik Advokatske komore Vojvodine)
This paper addresses the formal and practical challenges faced by the relevant Real Estate Cadastre Office when processing changes related to mortgaged real estate. When a mortgage is registered based on a mortgage agreement in the Cadastre database, it has legal implications. Making changes to a mortgaged real estate implies altering the subject of the mortgage. However, the real estate owner cannot change the subject of the mortgage without the consent of the mortgage creditor. Since any factual change requires proper registration in the Real Estate Cadastre, it is essential to submit the necessary documents that serve as the legal basis for registration. The paper also examines specific cases that involve making changes to the subject of the mortgage.